2008
DOI: 10.1017/s002211200800030x
|View full text |Cite
|
Sign up to set email alerts
|

Unsteady flows in pipes with finite curvature

Abstract: Motivated by the study of blood flow in a curved artery, we consider fluid flow through a curved pipe of uniform curvature, δ, driven by a prescribed oscillatory axial pressure gradient. The curved pipe has finite (as opposed to asymptotically small) curvature, and we determine the effects of both the centrifugal and Coriolis forces on the flow. In addition to δ, the flow is parameterized by the Dean number, D, the Womersley number, α, and a secondary streaming Reynolds number, R s . Asymptotic solutions are d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 27 publications
3
15
0
Order By: Relevance
“…Thomas et al (2011) have found neutrally stable conditions for pulsating pipe flow that could be used as starting points for nonlinear simulations; these conditions, however, correspond to essentially oscillating flow with a weak steady component, thus complicating their continuation toward physiological conditions. Furthermore, pulsatile flow through curved pipes (Siggers & Waters 2008) probably sustains even more complex dynamics.…”
Section: Summary and Future Workmentioning
confidence: 99%
“…Thomas et al (2011) have found neutrally stable conditions for pulsating pipe flow that could be used as starting points for nonlinear simulations; these conditions, however, correspond to essentially oscillating flow with a weak steady component, thus complicating their continuation toward physiological conditions. Furthermore, pulsatile flow through curved pipes (Siggers & Waters 2008) probably sustains even more complex dynamics.…”
Section: Summary and Future Workmentioning
confidence: 99%
“…1) can be leveraged to manipulate flow and oxygen transport patterns within AVF. Whilst flow in curved pipes has been studied extensively before, [25][26][27][28] we believe the concept of leveraging arterial curvature to manipulate flow in AVF to be novel.…”
Section: -2 Iori Et Almentioning
confidence: 99%
“…The study of flows in curved geometries has been motivated by flows in rivers and pipes (Thomson 1876(Thomson , 1877Dean 1927Dean , 1928, the circulatory system (Lynch et al 1996;Siggers & Waters 2005, 2008, and the cochlea (Manoussaki & Chadwick 2000). The impact of Dean's work was such that these flows are often termed "Dean flow".…”
Section: Introductionmentioning
confidence: 99%